Adoption of Quality Control Measures in Centralised and Decentralised Prawn Peeling Units - A Comparative Study - Gupta, Iancy (Fishery Technology, 2025)
A comparative study on the infrastructural measures adopted in centralised and non centralised prawn peeling units was carried out. lt was found that the centralised prawn peeling units had significantly high infrastructural facilities related to quality control compared to non centralised peeling units. lmposition of quality control measures helped to improve the quality standards of peeling sheds considerably.